Localization of the auxin permease AUX1 suggests two functionally distinct hormone transport pathways operate in the Arabidopsis root apex - Swarup, Ranjan (Cold Spring Harbor Laboratory Press, 2001)
Auxins represent an important class of plant hormone that regulate plant development. Plants use specialized carrier proteins to transport the auxin indole-3-acetic acid (IAA) to target tissues. To date, efflux carrier-mediated polar auxin transport has been assumed to represent the sole mode of long distance IAA movement. Localization of the auxin permease AUX1 in the Arabidopsis root apex has revealed a novel phloem-based IAA transport pathway. AUX1, asymmetrically localized to the plasma membrane of root protophloem cells, is proposed to promote the acropetal, post-phloem movement of auxin to the root apex. MS analysis shows that IAA accumulation in aux1 mutant root apices is impaired, consistent with an AUX1 phloem unloading function. AUX1 localization to columella and lateral root cap tissues of the Arabidopsis root apex reveals that the auxin permease regulates a second IAA transport pathway. Expression studies using an auxin-regulated reporter suggest that AUX1 is necessary for root gravitropism by facilitating basipetal auxin transport to distal elongation zone tissues.